“Intervención de enfermería en gestante con preeclampsia” - Gavilanes Romero , Magdalena Elizabeth (2024)
Preeclampsia is a specific hypertensive disorder of gestation, whose importance lies in the fact that it is one of the main causes of maternal and perinatal morbidity and mortality in the world in places with scarce economic resources. This condition is characterized as one of the hypertensive pathologies that occurs from the 20th week of gestation accompanied by the presence of proteinuria in the urine. Preeclampsia can be associated with several factors that can cause this problem, including obesity, family history of hypertension, diabetes, nulliparity, adolescent pregnancy, maternal age, stress and poor prenatal control. The purpose of this case study was to analyze the health of a pregnant woman with preeclampsia and twin pregnancy, with a particular vision of nursing interventions, providing care in a comprehensive and humanistic manner that includes communication, spiritual and emotional aspects for recovery and improvement of her quality of life. The patient underwent an exhaustive evaluation, considering her family history and risk patterns with the aim of improving the complications associated with pregnancy. According to the patient's follow-up, a favorable evolution was observed, highlighting the integral nature of nursing care not only during the pregnancy period, but also during the surgical process and the subsequent recovery stages, since it is the responsibility of health professionals to provide support and guarantee quality care to pregnant women in order to reduce maternal and fetal deaths